2013
DOI: 10.7241/ourd.20133.91
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmose africaine disséminée chez un enfant immunocompétent au Burkina Faso: un cas [Disseminated African Histoplasmosis in an immunocompetent child in Burkina Faso: one case]

Abstract: Introduction: L'histoplasmose à Histoplasma capsulatum var. duboisii est une affection rare en Afrique. Les lésions cutanées localisées sont les plus fréquentes. Nous rapportons une forme disséminée chez un enfant immunocompétent. Observation: Une élève de 8 ans est hospitalisée pour des nodules cutanés, généralisés, associés à des douleurs ostéo-articulaires très intenses de la quasi-totalité des articulations. L'examen a noté une malnutrition aiguë modérée, des nodules sous cutanés, multiples, des papules ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…In our patient, there was improvement with a reduction in papules and healing of abscesses. Barro-Traoré et al (2017) reported therapeutic failure with fluconazole after 4 months and 21 days of treatment, marked by a progressive recurrence of cutaneous and lymph node lesions, worsening of bone lesions, and hepato-splenic extension [24]. Although no recurrence was observed in our patient, it is necessary to monitor lesions in patients treated with fluconazole, especially in countries where amphotericin B (the reference molecule) is not easily accessible [4].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In our patient, there was improvement with a reduction in papules and healing of abscesses. Barro-Traoré et al (2017) reported therapeutic failure with fluconazole after 4 months and 21 days of treatment, marked by a progressive recurrence of cutaneous and lymph node lesions, worsening of bone lesions, and hepato-splenic extension [24]. Although no recurrence was observed in our patient, it is necessary to monitor lesions in patients treated with fluconazole, especially in countries where amphotericin B (the reference molecule) is not easily accessible [4].…”
Section: Discussionmentioning
confidence: 74%
“…Our patient presented with disseminated form, however, her HIV serology was negative despite being febrile and having an altered general state. It is worth noting that some authors have described disseminated forms in immunocompetent patients who are HIV negative [21,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic modalities for histoplasmosis used in the cases reviewed were mostly histopathology ( n = 33, 75%). Others included microscopy ( n = 3,6.8%), bone marrow aspirate and cytology ( n = 3,6.8%), culture ( n = 1,2.3%), and serology ( n = 1,2.3%) 11 16 , 22 35 , 37 , 41 – 44 , 46 Molecular diagnosis was not used in any of the cases. The diagnosis of histoplasmosis in children can be challenging.…”
Section: Resultsmentioning
confidence: 99%
“…L'histoplasmose à Histoplasma capsulatum var. duboisii ou histoplasmose à grandes formes est une affection rare mais non exceptionnelle en Afrique [5,6]. Cette rareté pourrait probablement s'expliquer par une errance diagnostique fréquente.…”
Section: Discussionunclassified